An evaluation of changes in farming systems in Co Phap cooperative, Red River Delta, Vietnam - Le Quoc Doanh; Suthad Setboonsarng; Upasena, Selawa H.; Demaine, Harvey; Thai King's Scholarship (Bangkok : Asian Institute of Technology, 1992)
The Red River Delta is a main rice production region of Vietnam. The government launched the reform in agricultural policies in 1987. This brought about a remarkable change in farming systems in the region. This study aims to investigate the changes in fanning systems and to dete1mine factors that contribute towards the improvement of the agricultural production in the Red River Delta. Major attributes of farming system in 1988 and 1990 were examined. Changes in farm activities and farm income were dete1mined, gross margins of rice, garlic, sweet potato and pig production in two years were also estimated. The Cobb-Douglas production function was applied for dete1mining the relationship between inputs and outputs in the production of rice, garlic and pig. The results of this study showed that: - Farm income increased very rapidly at rate about 35 percent in two years. Garlic contributed a high proportion in the increase of farm income. The growing areas under winter crops have expended remarkably, particularly garlic. There was an increase in input use during two years period. The yields of crops and pig also have increased. - Gross margin of garlic was very high as compared to other enterprises in this system. It varied from US$ 1130 to US$ 1784 in 1988 and from US$ 1570 to US$ 2436 in 1990. Gross margins of all crops and pig have increased quickly in two years. - Economic optimum of inputs for rice, garlic and pig was estimated. Generally, economic optimum of fertilizer inputs were higher than actual fertilizer use while the economic optimum of labor input was in contrast. - When farm income increased, non-food expenditure also increased rapidly at the rate about 85 percent during two years period.
A thesis submitted in partial fulfillments of the requirements for the degree of Master of Science, school of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1992
Keywords: Agricultural systems -- Vietnam